The Development of Artificial Learning Media to Fasilitate Active Learning to Improve Learning Outcome on The Teaching of Gas Chromatography - Safitri, Rahma; Situmorang, Manihar (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
The aim of this research is to develop artificial learning media to facilitate active learning to improve student learning outcomes in gas chromatography material separation chemistry, determining the suitability of website media as assessed by material expert validators, learning experts, and design experts, as well as describing the effectiveness of this media in improving student learning outcomes on the concept of gas chromatography. This Research and Development uses the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). Test the product conducted in small groups consisting of 27 students from two classes. Expert material, prayer a learning expert, two design experts, and pre-test and post-test results were used collect data, which is then explained and described. Validators stated that website media was suitable for use in the learning process with an average score of: 93.5%, 95.3%, and 97.2% with very feasible criteria and media created by this website has been effective in improving student learning outcomes and can be used in learning process. The average pre-test score is 70.65/150 while the average post-test score is 124.25/150 obtained. with a standard error of 0%, and effectiveness reaching 90% using Shapiro Wilk data processing in SPSS 16